Inclusive Leadership In Education: Transforming School Culture Through Equity, Empathy, And Digital Innovation - Winanti Natasya Larosa; Eka Periaman Zai (CV. SINAR HOWUHOWU, 2025)
The rapid evolution of global education systems in the digital era requires leadership models that not only prioritize academic excellence but also cultivate inclusive, empathetic, and equitable school cultures. This study explores the transformative role of inclusive leadership in fostering a culture of equity, empathy, and digital innovation within educational institutions. Grounded in the theoretical framework of transformational and inclusive leadership, this research investigates how school leaders integrate digital technologies to promote inclusive practices that address diverse learner needs. Using a mixed-method approach involving surveys and interviews with teachers and administrators across 20 schools, the study examines the relationships between inclusive leadership behaviors, digital inclusion strategies, and school culture transformation. Findings reveal that inclusive leaders who emphasize empathy-driven decision-making, equitable digital access, and collaborative innovation significantly improve teacher morale, student engagement, and institutional adaptability. Moreover, digital innovation acts as a key enabler for fostering participation and reducing barriers in educational communities. The research concludes that sustainable educational transformation in the 21st century requires leaders to embrace inclusivity not only as a moral imperative but also as a strategic framework for digital equity and cultural growth. These insights provide a foundation for policy formulation, leadership training, and the redefinition of school management paradigms toward more inclusive and future-ready learning environments.